Imaging of pediatric central nervous system tumors (2017)
Central nervous system (CNS) tumors are the most common type of solid tumors in the pediatric population. Neuroimaging is the sine quo non for state-of-the-art care of pediatric patients with central nervous system neoplasms. A variety of noninvasive imaging techniques are described which have shown utility in patient care from the time of initial diagnosis to surgical and radiation planning and then also during posttreatment surveillance for treatment effects, complications and to exclude recurrent disease. This overview of imaging techniques will hopefully give the reader a better understanding in choosing appropriate imaging strategies for optimal individualized patient care. © Springer International Publishing AG 2018.